PENGARUH KEMTRAAN TERHADAP KINERJA USAHA MIKRO DAN KECIL TAHU DI INDONESIA - Rizky Ariesty Fachrysa Halik; Amzul Rifin; Siti Jahroh (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
A partnership is a form of cooperation that is needed to be done for business development so that it can be globally competitive. With the existence of a partnership, it can improve the ability of small businesses through capital support and professional resource training to increase business income and continuity. In Indonesia, tofu business is one of the micro and small businesses that have the potential to be developed. To improve business performance, it is necessary to collaborate among tofu businesses and large businesses or state-owned enterprises. The purpose of this study was to analyze the effect of partnerships and other factors on the performance of the tofu business in Indonesia. Tofu businesses can be grouped into two categories, namely partner and non-partner businesses. To estimate the performance of tofu businesses in Indonesia, multiple linear regression method was used. The data used in this study were collected from the Central Bureau of Statistics and the Ministry of Cooperatives and SMEs, in which 237 tofu businesses were taken as samples. The results showed that partnership had a positive and significant impact on tofu businesses income. Besides, business life, raw material cost, labour force and marketing allocation also positively significant affected tofu businesses income. However, the level of education, the age of the entrepreneur, the number of tools used, business capital, training, sales distribution, and cooperatives did not significantly affect tofu businesses income